Vapour or dipping applications of methyl jasmonate, vinegar and sage oil for pepper fruit sanitation towards grey mould - Tzortzakis, Nikos G.; Chrysargyris, Antonios; Sivakumar, Dharini; Loulakakis, Konstantinos A. (My University, 2016)
Grey mould (Botrytis cinerea) development in vitro or on pepper (Capsicum annuum) fruit was evaluated after treatment with chlorine (CHL), methyl jasmonate (MJ), vinegar (VIN), or sage oil (SAG) and storage at 11 °C and 95% relative humidity following sanitary exposure (volatiles or dipping). Fruit treated (up to 12 days) with MJ and SAG vapours reduced lesion development and spore production while no differences were found for spore germination. The benefits associated with volatile enrichment was maintained in fruit pre-exposed to MJ and SAG oil vapours, resulting in suppression of lesion growth, while fungal reproduction decreased only in SAG pre-exposed fruit. Studies performed on fungi grown on Potato Dextrose Agar (PDA) revealed colony growth suppression and spore production for direct SAG vapour application or PDA pre-exposed to SAG following B. cinerea inoculation, implying that suppression of pathogen development was mainly due to the impact of volatiles on fruit-pathogen interactions and/or residual effects on fruit tissue and/or medium culture. In vitro, fungal biomass was examined under different concentrations (10-50-100-500-5000 μL L-1) and was accelerated in high SAG concentrations, while spore production decreased (including MJ and VIN) on fungi grown in Potato Dextrose Broth (PDB), implying the effects to be concentration dependent. Moreover, sanitary dips proved to be less effective in fruit sanitation compared to vapour application. The results of this study indicate that SAG-, followed by MJ volatiles may be considered as alternatives to the traditional postharvest sanitising techniques. Each commodity needs to be individually assessed, and the volatile concentration and sanitising technique optimised, before commercialisation.
Keywords: Botrytis cinerea; Signalling compounds; Capsicum annuum; Decay; Essential oil; Sanitation